2014
DOI: 10.1186/1710-1492-10-41
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the main allergen sensitizers in an Iran asthmatic population by molecular diagnosis

Abstract: BackgroundThere has been a significant growth in the prevalence of allergy, mainly associated to IgE-mediated disorders such as asthma and rhinitis. The identification of atopy in asthmatic patients through the measurement of specific IgE can help to identify risk factors that cause asthmatic symptoms in patients. The development and use of individualized allergen-based tests by the Component Resolved Diagnosis has been a crucial advance in the accurate diagnosis and control of allergic patients. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…139 In Iran, IgE in 202 adult asthmatic patients was directed against the grass pollen allergens Phl p 1 and 5, but even more to Salsola kali (Sal k 1), which is an important pollen source in this area. 140 However, the authors did not find a correlation between IgE levels and asthma symptoms.…”
Section: Pollensmentioning
confidence: 90%
“…139 In Iran, IgE in 202 adult asthmatic patients was directed against the grass pollen allergens Phl p 1 and 5, but even more to Salsola kali (Sal k 1), which is an important pollen source in this area. 140 However, the authors did not find a correlation between IgE levels and asthma symptoms.…”
Section: Pollensmentioning
confidence: 90%
“…34 Animal Dander Exposure to animal dander rapidly induces respiratory symptoms in individuals who are sensitive to cat or dog dander or any kind of bird feather. Farrokhi et al 5 and Khazaei, 26 found that the prevalence of feather allergies was 78.5%, and 70% in Bushehr, Sistan and Baluchistan, respectively. The lower prevalence of allergies to feathers than to cat dander may be due to genetic factors or to a lower exposure to birds than to cats in the Iranian populations.…”
Section: Arthropods and House Dust Mitesmentioning
confidence: 98%
“…There are approximately 100,000 pollen allergens; however, only anemophilous plants (which produce large quantities of tiny pollen grains that become airborne for days with a density higher than 25 grains per cubic meter of air), can initiate an allergy [23]. The prevalence of allergies to pollen grains has increased in past years, rising up to 86.7% of the allergic patients in different cities, depending on phytogeography, humidity, air pollution and temperature conditions [24][25][26][27][28][29]. According to local studies, there are three main sources of pollen allergens in Iran.…”
Section: Pollen Grainsmentioning
confidence: 99%